Glutathione‐Gated Potassium Efflux as a Mechanism of Active Biofilm Detachment. (1st May 2014) - Zhang, Wen; McLamore, Eric S.; Wu, Ruoxi; Stensberg, Matthew; Porterfield, D. Marshall; Banks, M. Katherine
ABSTRACT: Biofilm detachment often has detrimental effects such as pipe obstruction and infection, yet the detachment mechanisms underlying dispersal remain largely unknown. In this study, a stress response mechanism known as glutathione‐gated potassium efflux (GGKE) was evaluated as an active detachment mechanism in the dispersal of Pseudomonas aeruginosa biofilms. N‐ethylmaleimide (NEM) was used to activate potassium efflux proteins (Kef) associated with the GGKE pathway. This stress response mechanism was hypothesized to lead to altered cation concentration, which can potentially affect polymer bridging in biofilms, and ultimately cause biofilm detachment. Results showed the activation of GGKE by NEM exposure caused biofilm detachment without inducing a measurable change in viability, and detached biomass concentration and composition were dependent on NEM concentration. More detached biomass was observed with higher concentrations of NEM, with a trend of increasing polymer detachment. The detachment was likely resulting from a weakened biofilm structural integrity induced by bridge denaturing from GGKE activation. This study is important in understanding biofilm detachment from engineered systems such as membrane aerated bioreactors.